ALTERNATIVE SOCIAL CONTROL SYSTEMS - Pepinsky, Hal (TRAILS: Teaching Resources and Innovations Library for Sociology, 2010)
My overarching objective for this class is to create an environment in which each and every one of us gains significant control of her or his own relations. That could include coming out of class with new choices you can make, for instance, to give and receive respect, as on police patrol with civilians, as offenders to victims, as parent with a child, as a partner or friend, or as a national government with one’s own people and internationally. In the process, I hope you also get a clearer sense of where you might most want to contribute to social control—develop your own sense of where social control is most immediate to you or matters most to you.